PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS BINA MARGA PROPINSI SULAWESI TENGAH - Sutoyo, Sutoyo (Katalogis, 2016)
This research aims to explore and analyze simultaneous and partial impacts of workload, wor environment, and motivation on employee performance in Bina Marga Agency of Centra Sulawesi. It involves 99 employees as respondentsand applies multiple linear regressions analysis with descriptive approach. The results indicate that workload, work environment, and motivation simultaneously and partially have significant influence on employees’ performance in Bina marga Agency of Central Sulawesi.